2005
DOI: 10.1353/dem.2005.0016
|View full text |Cite
|
Sign up to set email alerts
|

Migration and relationship power among mexican women

Abstract: Our study drew on original data collected in Durham, NC, and four sending communities in Mexico to examine differences in women's relationship power that are associated with migration and residence in the United States. We analyzed the personal, relationship, and social resources that condition the association between migration and women's power and the usefulness of the Relationship Control Scale (RCS) for capturing these effects. We found support for perspectives that emphasize that migration may simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 55 publications
4
85
2
2
Order By: Relevance
“…The divergent results for the relationship control subscale have also been noted in recent studies 60,61 and may indicate that it is capturing more than one construct. Prior studies have found higher total SRPS scores to be associated with fewer unprotected sexual occasions in a community sample 13 and substance abuse treatment-seeking sample.…”
Section: Discussionmentioning
confidence: 68%
“…The divergent results for the relationship control subscale have also been noted in recent studies 60,61 and may indicate that it is capturing more than one construct. Prior studies have found higher total SRPS scores to be associated with fewer unprotected sexual occasions in a community sample 13 and substance abuse treatment-seeking sample.…”
Section: Discussionmentioning
confidence: 68%
“…Studies elsewhere have shown that forced sex increases the risk of contracting HIV since in most of these scenarios; no condoms are used 14,8,29 . This study also set out to determine the association between post-migration environments and power imbalances between men and women which, according to Parrado et al determine condom use 19 . One of the major propositions was that labour migration tends to increase women's financial stability which in turn increases women's negotiating power.…”
Section: Discussionmentioning
confidence: 99%
“…In analysing the factors associated with condom use, this study borrows from the Resource Theory of Power as it is applied by Parrado et al and the Conceptual Model of Temporary Migration and HIV risk behaviour by Yang 19,20 . The former theory alludes to the power dynamics in relationships, while the latter conceptualises the connection between post-migration socioeconomic environments and HIV risk behaviours.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Mexican immigrants specifically, scholars underscore that husbands' marital satisfaction and the interaction between gender role attitudes and wives' paid employment is nested within the context of migration (Hondagneu-Sotelo, 1992). It has been argued that many families who move to the United States encounter a system that favors a sex-typed gender role ideology, but demands contradicting behaviors from women (Baker, 2004;ChaviraPrado, 1992;Parrado, Flippen, & McQuiston, 2005). Macro social forces in the US (e.g., a lack of sufficient jobs for men) lead women to violate sex-typed behavioral role expectations that discourage wives' employment, but because women violate norms primarily for the well-being of their husbands and children, sex-typed values are challenged and reinforced simultaneously (Baker, 2004).…”
Section: Status and Husbands' Marital Satisfactionmentioning
confidence: 99%